IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN ANALYTICAL EXPOSITION TEXT BY USING ROUNDTABLE TECHNIQUE AT SECOND GRADE STUDENTS OF MAN KRECEK PARE - kamila, Mila (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study aims to know Improving Students’ Writing Achievement in Analytical Exposition Text by Using Roundtable Technique at Second Grade Students of MAN Krecek Pare. It used class room action research (CAR).The subject of this research were second grade students of IPS 2 at MAN Krecek Pare that consisted of 16 males and 22 females. Based on the result of the pre-test which was carried out in the preliminary, it showed that the subjects’ writing analytical exposition text was categorized as insufficient, which was 67.47. The present classroom action research then was carried out by implementing roundtable technique in two-planned cycles. From the technique implemented, (1) in cycle I there was significant improvement from the subjects’ writing analytical exposition text, in which it improved from insufficient to good, which was 74.02 (2) cycle II there was significant improvement from the subjects’ writing analytical exposition text, that the mean score was 80.71. Furthermore, the research could bring the improvement to the subjects’ writing analytical exposition text by implementing the technique. To sum up, the present classroom action study proved that roundtable technique could improve the writing achievement of the second grade students of IPS 2 at MAN Krecek Pare. In addition, the factors that influence the improvement of students’ achievement in writing were teacher’s factor (classroom management and teacher’s explanation) and student’s factor (students’ attention, participation and interest).